Pengaruh Pengelolaan Good Corporate Governance, Ukuran Perusahaan dan Profitabilitas Terhadap Nilai Perusahaan: Studi Kasus Industri Perbankan Syariah yang Terdaftar di BEI Periode 2020-2023 - Mujiono S; Iskandar Zulkarnain (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to test and analyze the effect of Good Corporate Governance, Company Size and Profitability together on Company Value in the Islamic Banking Industry listed on the IDX in 2020-2023. This research is a quantitative method and is associative in nature. The population in this study were 4 Islamic banking companies. The sample in this study used saturated samples, namely 4 Islamic banks with a period of 4 years, the number of observations was 16 times. This research data is secondary data. The data analysis tool uses multiple linear regression with eviews 12 software. The conclusions that can be drawn in this study are that there is a positive influence between good corporate governance on firm value, there is a negative and significant influence between company size on firm value, there is a positive and insignificant influence between profitability on firm value in Islamic Banking listed on the IDX from 2020 to 2023, and there is a simultaneous significant influence (together) between good corporate governance, company size and profitability on firm value variables in Islamic Banking listed on the IDX from 2020 to 2023.